EFEITO DE PRODUTOS ALTERNATIVOS PARA O CONTROLE DA ANTRACNOSE EM FEIJÃO - Truylio, Carlos Eduardo Carbonar (2015)
management of crop diseases. The objective of this study was to evaluate different alternative products against anthracnose, with the detached leaf assay method, and in field conditions in common beans. The experiment with detached leaf assay method was conducted in laboratory. The experimental design was completely factorial randomized in a factorial arrangement 10 (treatment) x 2 (application or not in half the leaf) with 5 repetitions. The evaluation of severity and area under the anthracnose progress curve was performed. The experiments under field conditions were conducted in 2013/2014 and 2014/2015 harvest, at Fazenda Escola Capão da Onça. The experimental had a randomized blocks design, with four repetitions. The evaluation of severity, area under the disease progress curve and anthracnose index in the pods, in addition to crop production components were performed. The treatments for the experiments were: 1- V- 6 (Meristem enzymes, 5,4%; Mn, 2,5%; Zn, 1,9%; Mo, 0,16%), 2- Wert plus (toxins produced by cultivating from different microorganisms, such as Bacillus subtilis, Gliocladium catenulatum, Trichoderma sp, Trichoderma harzianum, Azotobacter chroococcum, e micronutrients Cu, Zn e Mg), 3- High Roots (12% of seaweed; 4,8% of K2O; 0,2% of CaO), 4- Max Fruit (4,61% of calcium), 5- Rocksil (20,56% of Al2O3, 17,43% of SiO2; 9,82% of S; 1,31 of CaO; 0,34% of TiO2; 0,18 of MgO; 0,16% of Fe2O3; 0,1% of P2O5), 6- Herbagreem (36,7% of CaO; 17 to 20% of SiO2; 2,4% of MgO; 3,4% of Fe2O3; 0,7% of K2O; 0,5% of Na2O; 0,4% of SO3; 0,2% of P2O5; 0,1% of MnO; 1 mg kg-1 of B; 13 mg kg-1 of Co; 26 mg kg-1 of Cu; 34 mg kg-1 of Zn), 7-Fluisan (hop extract: 80,7 %), 8- Herbagreen + Fluisan, 9- trifloxystrobin + tebuconazol and 10- control. In the detached leaf assay, Wert Plus had a negatively influence, increasing the severity of the disease. At field conditions, there was no statistical difference in severity between treatments in both harvests. The Wert Plus treatment had a higher rate of anthracnose on pods in 2013/2014 harvest. The yield components of culture, number of plants per meter, number of pods per plant, number of seeds per pod, weight of 100 grains and productivity were not affected by treatments.